THE RELATIONSHIP OF POSTPARTUM MOTHER’S AGE FACTORS WITH THE INCIDENT OF BABY BLUES IN THE WORKING AREA OF CIMALAKA HEALTH CENTER WEST JAVA - Aam Lisaadah; Emi Lindayani; Iyos Sutresna (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Baby blues is a mental health disorder that attacks women who give birth in the first week of pregnancy, which can be caused by husbands, friends, family and other acquaintances rarely showing concern for the health of postpartum mothers during this time. If this is not handled properly, the disorder can get worse and cause postpartum depression or postpartum psychosis. Age affects a person's physical, emotional and psychological maturity, so age increases the chance of developing baby blues. Age factors that can cause Baby Blues are mothers who give birth under 20 years and over 35 years. Mothers who give birth for the first time experience higher levels of stress than mothers who have given birth before. This study aims to determine the relationship between postpartum maternal age and baby blues in the Cimalaka Community Health Center working area. This research uses a quantitative descriptive correlation method with a Cross Sectional approach which examines the relationship between variables using the Spearman Rank statistical test. In this study, researchers examined the relationship between postpartum maternal age variables and the incidence of baby blues in the Cimalaka health center working area. The total population is 150 and the sample is 60 with sampling using a systematic random sampling method where only postpartum mothers aged < 2 months are willing to fill out and become respondents. The results of this study showed that there was no significant relationship between postpartum maternal age and the incidence of baby blues in the Cimalaka Community Health Center working area with a p-value = 0.794 > alpha, with the strength of the relationship being no relationship and in the negative direction with a value of r = - 0.034.